Investigation of the surface properties of dibutyl amine modified poly(styrene) based polymer by inverse gas chromatography method - Adiguzel, A. C.; Korkmaz, B.; Cakar, F.; Cankurtaran, O.; Senkal, B. F. (SPRINGER, 2021)
In the present study, poly(vinyl benzyl chloride) (PVBC) was prepared by the radical polymerization method. Then, PVBC was reacted with dibutyl amine to obtain tertiary amine-modified poly(styrene) based polymer (PVBC-Dibutyl amine) and the resulting polymer was characterized. Surface properties of the polymer were investigated by inverse gas chromatography method at infinite dilution region. For this purpose, the retention diagrams of carefully selected polar and non-polar solvents (probes) on PVBC-Dibutyl amine were obtained over a temperature range from 30 to 50 degrees C. By using the diagrams, the dispersive component of the surface free energy of the polymer surface was calculated for the studied temperatures by two different methods. The specific enthalpy of adsorption and the specific component of the adsorption free energy of solvents on PVBC-Dibutyl amine which are adsorption thermodynamic parameters were determined for each solvent used. Using the adsorption data, Lewis acid and Lewis base parameters of PVBC-Dibutyl amine surface were calculated. The obtained parameters reflected that surface of PVBC-Dibutyl amine exhibited a basic behavior. Considering the values in the literature, the effect of dibutyl amine moieties in the structure of poly(styrene) based polymer PVBC-Dibutyl amine on the dispersive surface free energy and acid-base parameters of poly(styrene) was discussed.
Keywords: Functional polymer; Inverse gas chromatography; Surface characteristics; Dispersive surface free energy; Acid-base properties; Polymer Science